Spin-dependent transport in magnetic sandwiches in the effective-mass approximation - Los’, V.F.; Saltanov, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
A theory describing a spin-dependent transport of electrons through a thin metallic (or insulator) nonmagnetic layer sandwiched between two ferromagnets is developed in the ballistic regime and current-perpendicular-to-plane (CPP) geometry. The theory is based on the Landauer formalism and the transmission amplitude for the electron Bloch waves with an arbitrary dispersion law travelling from one ferromagnet to another through a nonmagnetic spacer (metallic or insulator). The semiclassical (non-oscillating) part of the magnetoresistance ratio for a metallic spacer is considered in the effective-mass approximation for the sandwich band structure. The parameters defining the value of the giant magnetoresistance (GMR) effect are obtained. It is shown that the electron specular scattering on the interfaces may be the cause for the CPP GMR effect. The influence of the electronic structure on the CPP GMR effect has been studied numerically in the effective-mass approximation.